2018
DOI: 10.1111/ics.12494
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an agonist of αMSH, the palmitoyl tetrapeptide‐20, in hair pigmentation

Abstract: The current findings demonstrate the ability of the biomimetic PTP20 peptide to preserve the function of follicular melanocytes. The present results suggest potential cosmetic application of this newly designed agonist of α-MSH to promote hair pigmentation and thus, reduce the hair greying process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A previous study showed that SIRT-1 enabled mitochondrial homeostasis against the stress caused by TNF-α-dependent mediators on the hair follicle and increased the stem cells in the hair follicle as a way of protection [ 44 ]. Another study concluded that the decrease in hair pigmentation in chronological aging might be prevented by increasing the levels of SIRT-1 [ 45 ]. In an experimental study, it was determined that arginine increased the expression of SIRT-1 and MMP-2, reduced myocardial fibrosis and prevented cell apoptosis in streptozotocin-induced diabetic rats [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that SIRT-1 enabled mitochondrial homeostasis against the stress caused by TNF-α-dependent mediators on the hair follicle and increased the stem cells in the hair follicle as a way of protection [ 44 ]. Another study concluded that the decrease in hair pigmentation in chronological aging might be prevented by increasing the levels of SIRT-1 [ 45 ]. In an experimental study, it was determined that arginine increased the expression of SIRT-1 and MMP-2, reduced myocardial fibrosis and prevented cell apoptosis in streptozotocin-induced diabetic rats [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…PTP20, an α-MSH agonist, has been reported to enhance the expression of catalase and to decrease (by ~30%) the intracellular level of H 2 O 2 in both in vivo and in vitro studies. [ 10 ] Furthermore, PTP20 has shown to activate the melanogenesis process in vitro and ex vivo , which has shown to be correlated with elevated expression of MC1-R, TRP-1, and with the reduction in ASIP expression. It is also associated with modulation on TRP-2.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding pharmacotherapy of PGH, although many agents, for example, p-amino benzoic acid, 15 calcium pantothenate, 12,13 palmitoyl tetrapeptide-20 lotion, 16 anti-aging compounds, 2 and herbal agents 17 have been used, the grades of recommendation are low (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Although, it is used in many settings, 16,19 we could not find any study, using melanocyte grafting for the purpose of treatment of PGH.…”
Section: Melanocyte Graftingmentioning
confidence: 95%
See 1 more Smart Citation